Modulations of Inter-Hemispherical Phase Coupling in Human Single Leg Stance. (15th March 2020) - Lehmann, Tim; Büchel, Daniel; Cockcroft, John; Louw, Quinette; Baumeister, Jochen
Highlights: Cortical activation is modulated with increasing postural instability. Increased postural sway was associated with increased cortical excitability. Phase coupling decreased from bipedal to single leg stance. Task-specific inhibition of motor networks may favor postural control. Abstract: Introduction: Recent findings from neuroimaging studies provided initial insights into cortical contributions to postural control. These studies observed enhanced cortical activation and connectivity when task-difficulty and postural instability increased. However, little attention has been paid to the allocation of cortical networks appearing with a decreasing base of support from bipedal to single leg stance. Therefore, the aim of the present study was to investigate modulations of functional connectivity from bipedal to single leg stance. Experimental procedures: Cortical activity during bipedal and single leg stance ( left ) was investigated in 15 male subjects using 128 channel mobile electroencephalography (EEG), while standing on a triaxial force plate. Power spectral density was calculated for theta (4–7 Hz), alpha-1 (8–10 Hz) and alpha-2 (10–12 Hz) frequency bands. Estimations of the phase lag index (PLI) were conducted as a measure of functional connectivity. Moreover, postural control was analyzed by the area of sway and sway velocity. Results: The results demonstrated a significantly increased area of sway and decreased alpha-2 power in single leg compared to bipedal stance. Furthermore, PLIs within the alpha-2 frequency band showed significantly decreased inter-hemispherical phase coupling in single leg stance, associated with connections involving the left motor region. Discussion: Altogether, the present findings may indicate modulations of cortical contributions in single leg compared to bipedal stance. The present data suggest that decreased inter-hemispherical functional connectivity, in conjunction with a global increase in cortical excitability, may indicate enhanced alertness and task-specific selective inhibition of motor networks in favor of postural control.